Klasifikasi dan Kodefikasi Diagnosis Infeksi, Parasit, Neoplasma, Cedera, Keracunan, dan Penyebab Luar di RSUD Embung Fatimah - Ernaman Putri, Riza Suci; Putri, Widya; Triani, Melfina (Jurnal Kesehatan Komunitas, 2025)
Medical records play an important role in supporting quality health services, one of which is through accurate diagnosis classification and coding. This study aims to analyze the classification and coding of diagnoses of infection, parasites, neoplasms, injuries, poisoning, and external causes for the period of January 2025 at Embung Fatimah Hospital. The type of research used is quantitative research with a descriptive observational research design., conducted on January 20 - February 5, 2025. Data collection techniques were carried out through direct observation and documentation studies from the medical records unit. The number of samples analyzed was 40 out of 391 outpatient diagnosis data. The analysis technique used was descriptive analysis to identify and classify diagnoses. Of the 391 data it was found that, code S (injury) was the most common, with 180 cases, followed by code D (neoplasm), with 132 cases. The ten most common diseases include Vulnus Lacerasi (S31.4), Thalassemia (D56), and Superficial Injury of Head (S00). It was recommended that hospitals conduct routine audits of medical documents to ensure the accuracy of diagnoses.